EFFICACY OF RBCL AND TRNH-PSBA IN DIFFERENTIATING BETWEEN ORNAMENTAL AND MEDICINAL PORTULACA - Sumeyha, Fathimath (2018)
Portulaca oleracea and Portulaca grandiflora are widely used as medicinal herbs because of their various health benefits. Due to its increase demand people are selling false herbs, mixing low grade material or using substitutions that can lower the potency of the medicine. Hence the need arises to authenticate the identity of the species used as medicinal Portulaca. Plant identification can be very challenging but we need to identify the species, as any toxic plants if consumed mistakenly due to adulteration of medicinal herbs, can be detrimental to human health. Thus in this study we use DNA barcoding in which two plant molecular markers rbcL and trnH-psbA situated on the chloroplast was tested to determine if they can be used to identify Portulaca oleracea and Portulaca grandiflora species and compare them to the medicinal Portulaca obtained from traditional Chinese medicine center. DNA barcoding is a method in which a standardized region of the DNA of each plant species is used for identification. DNA barcoding is opted for this study as it is rapid, reliable and has high discriminative power compared to other molecular markers. Genomic DNA was extracted from ornamental P. oleracea, medicinal. P. oleracea and P. grandiflora and subjected to PCR amplification using rbcL and trnH-psbA markers followed by analysis of the quality of PCR product via agarose gel electrophoresis. Both rbcL and trnH psbA gene had a 100% PCR success rate. Sequencing success rate for rbcL in this study is 77.8% and for trnH psbA 88.9%, although only 11.1% of trnH psbA had consensus sequences with less than 1% mismatch. In BLAST analysis rbcL barcode had a 66.67% identification success while trnH psbA barcode had 44.4% success rate for species identification. Upon phylogenetic tree construction rbcL was only able to differentiate to genus level, while trnH psbA was able to differentiate up to the species level. From the results obtained, the identification method described is considered unreliable due to poor sequence quality. As such, this study suggests that while rbcL can be used as a barcode for Portulaca, the problem of poor sequence quality of trnH psbA needs to be resolved before it can be recommended for further use.